2010
DOI: 10.5539/jas.v2n1p180
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seedling Age at Inoculation and Cultivar on the Pathogenicity of a Virus Causing Yellow Mosaic Disease of Commelina Benghalensis L. on Cowpea

Abstract: A screenhouse experiment was conducted to evaluate the influence of seedling age at inoculation and cultivar on pathogenicity of the virus causing yellow mosaic disease of Commelina benghalensis L, a broad leaf weed, on cowpea. Three cowpea varieties namely Vita 5, IT84S2246D and Ife Brown were grown in pots and inoculated with sap extracted from leaves of C. benghalensis infected with yellow mosaic disease at 7, 14, and 21 days after germination (DAG). It was found that inoculation of cowpea seedlings at 7 DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…This resulted in a higher suppression of the pathogen population in soil, which leads to a decrease in disease severity and an enhancement in plant growth and yield. Similar results were obtained by Aliyu et al. (2010) , who reported increased yield and growth of cowpea by applying Azadirachta indica leaf powder at 14 DBT.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This resulted in a higher suppression of the pathogen population in soil, which leads to a decrease in disease severity and an enhancement in plant growth and yield. Similar results were obtained by Aliyu et al. (2010) , who reported increased yield and growth of cowpea by applying Azadirachta indica leaf powder at 14 DBT.…”
Section: Discussionsupporting
confidence: 89%
“…This resulted in a higher suppression of the pathogen population in soil, which leads to a decrease in disease severity and an enhancement in plant growth and yield. Similar results were obtained by Aliyu et al (2010), who reported increased yield and growth of cowpea by applying Azadirachta indica leaf powder at 14 DBT. The maximum safe amount of P. hysterophorus powder was then evaluated for managing bacterial wilt of tomato in field conditions by using the best application time 15 days before transplantation and method of application (mixing).…”
Section: A B Figuresupporting
confidence: 89%
“…In addition to its allelopathic effects on crops, the weeds appears to be an important virus pool, thus constituting a major constraint on efforts to increase and sustain food production [45]. As a key host for plant pathogens, Benghal dayflower is closely related to the outbreak of crop epidemics [13].…”
Section: Hazardsmentioning
confidence: 99%